Konsep Dan Peran Sistem Manajemen Basis Data Relasional Pada Sistem Informasi Manajemen - Yunda Adisa; Muhammad Irwan Padli Nasution (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
The increase in digital systems has led to an increasingly important need for information in the current era of globalization. Facilities and infrastructure in technology really support the success of an information so that it is conveyed properly and correctly. This is exemplified by the use of computers in people's lives which are used to facilitate work and in everyday life. Therefore, the role of a computer-based management information system is very much needed in order to provide a competitive advantage so that it can be prioritized on a high scale. With the presence of an information system, an agency, institution and organization will add value to obtain, manage, distribute and utilize information competitively and efficiently with the aim of improving organizational performance and making decisions to achieve the goals of the organization. If the information system is accurate and relevant, it can be used to support company decision making. But sometimes a bad database system on the system will produce problems. So the system must be continuously reviewed and modified to maintain its quality. So we need a number of relational schema relations and databases to produce a schema relation to store information properly and make decisions easily.